Drying Characteristics of Salted Fish in a Greenhouse-type Solar Dryer - Demir, Sebnem; Evcin, Serdar (Fishery Technology, 2025)
In Â this study, the drying characteristics of salted fish (Merlangius merlangus) were investigated by the drying experiments carried out in a greenhouse constructed for dehydration and augmented by parabolic reflectors. Drying time of samples was 26 h in the greenhouse and 38 h for samples dried outside to 25% moisture content. It was decided to apply thin layer drying theory in order to explain and compare drying characteristics. Drying constant of that equation was minimum for samples dried in the greenhouse on the conveyor belt augmented by solar reflectors.